Electronic decision support for treatment of hospitalized smokers: A qualitative analysis of physicians' knowledge, attitudes, and practices. (1st January 2019) - Grau, Lauretta E.; Weiss, June; O'Leary, Teresa K.; Camenga, Deepa; Bernstein, Steven L.
Highlights: Overall attitudes about the electronic medical record (EMR)-embedded tobacco use treatment tool were positive. Contextual factors in the inpatient environment influence use of the tool. Appropriateness of starting inpatient treatment for tobacco dependence was questioned. Adjusting suppression logic and when the intervention fires may improve usability. Additional decision support and training may also increase use of the tool. Abstract: Background: We recently demonstrated the ability of a suite of tools embedded in an electronic medical record (EMR) to improve tobacco cessation treatment for adult smokers admitted to the hospital. A randomized controlled trial conducted by our group demonstrated the ability of an EMR-embedded tobacco use disorder treatment tool, the Electronic Support Tool and Orders for the Prevention of Smoking (E-STOPS), to increase the identification and treatment of smokers, but its uptake varied among 126 physicians randomized to the intervention arm. The purpose of this study was to identify facilitators and barriers to using E-STOPS. Methods: Semi-structured individual interviews from a purposive sample of 12 hospitalist attending physicians and nine internal medicine residents who were randomized to the E-STOPS intervention were analyzed thematically. Results: Three themes shaped E-STOPS use: the inpatient environment, prescriber attitudes and beliefs, and information needs. Overall, participants were pleased with E-STOPS, but had specific suggestions for improvements regarding the timing of the intervention, suppression logic, and additional decision support and training. A few had concerns about the clinical appropriateness of beginning treatment for tobacco dependence during a hospitalization and the proper role of the inpatient team in that treatment. Conclusions: Tobacco dependence treatment for hospitalized smokers and facilitated by the EMR is generally acceptable to hospitalists and resident physicians. Improvements in provider training and feedback as well as the timing and content of the electronic tools may increase their utilization by inpatient physicians.